The vitality of the Daur language in Inner Mongolia, China - J Du (Journal of Modern Languages, 2025)
This article reports on research assessing the vitality of Daur, an ethnic language spoken mainly by Daur people residing in Inner Mongolia, China. The research involved a language use survey, individual interviews, and the EGIDS framework. Based on analysis of Daur use patterns in various domains and answers to the five key EGIDS questions, it is observed that Daur enjoys relatively low vitality (6b) and seems to be threatened in Inner Mongolia. The likely main causes for its relatively low vitality are the lack of a unified and widespread writing system and the small size of the speaker population. After presenting the findings and discussing the vitality level of Daur, this article concludes with some general implications and considerations for the maintenance of the Daur language in Inner Mongolia. This research sheds light on issues related to the vitality of ethnic languages in Inner Mongolia and seeks to contribute to the discussion on ethnic language maintenance in ethnic regions and areas in China.